Extruded linseed alone or in combination with fish oil modifies mammary gene expression profiles in lactating goats. (10th November 2017) - Faulconnier, Y.; Bernard, L.; Boby, C.; Domagalski, J.; Chilliard, Y.; Leroux, C.
Abstract : Nutrition is a major factor that regulates ruminant milk components, particularly its fatty acid (FA) composition, which is an important determinant of milk nutritional quality. In the mammary gland, milk component biosynthesis involves a large number of genes under nutritional regulation that are not well understood. Thus, the objective of the present study was to evaluate the effects of extruded linseeds (EL) alone or in combination with fish oil (ELFO) on goat mammary gene expression. In total, 14 goats were fed one of the following three diets: a natural grassland hay basal diet (CTRL) alone, CTRL supplemented with 530 g/day of EL, or 340 g/day of EL plus 39 g/day of fish oil (ELFO). Mammary secretory tissues were collected after slaughter on day 28, to determine the expression of 14 lipogenic genes and five lipogenic enzyme activities and transcriptomic profiles. The mRNA abundance decreased for SCD1 ( P <0.1) with ELFO v . CTRL, and for AZGP1 ( P <0.1) and ACSBG1 ( P <0.05) decreased with EL v . ELFO and the CTRL diets (only for ACSBG1 ), respectively. Transcriptomic analyses performed using a bovine microarray revealed 344 and 314 differentially expressed genes (DEG) in the EL and ELFO diets, respectively, compared with the CTRL diet, with 76 common DEGs. In total, 21 and 27 DEGs were involved in lipid metabolism and transport class in the EL and ELFO v. the CTRL diets, respectively, with eight common genes ( ALDH3B1, ALDH18A1, DGKD1, ENPP1, IL7, NSMAF, PI4KA and SERINC5 ) down-regulated by these two treatments. In EL v. CTRL diets, a gene network related to lipid metabolism and transport was detected. Although this network was not detected in the ELFO v . CTRL analysis, five genes known to be involved in lipid metabolism and transport were up-regulated ( SREBF1, PPARG and GPX4 ) or down-regulated ( FABP1 and ENPP6 ) by ELFO. The protein metabolism and transport biological processes were largely altered by both EL and ELFO v. CTRL diets without changes in major milk protein secretion. Amino acid metabolism was highlighted as an enriched network by Ingenuity Pathway Analysis and was similar to cellular growth and proliferation function. Two regulation networks centered on the estrogen receptor (ESR1) and a transcriptional factor (SP1) were identified in EL and ELFO v . CTRL diets. In conclusion, these results show that these two supplemented diets, which largely changed milk FA composition, had more effects on mRNA linked to protein metabolism and transport pathways than to lipid metabolism, and could affect mammary remodeling.